2021
DOI: 10.3389/fcell.2021.718466
|View full text |Cite
|
Sign up to set email alerts
|

The Off-Targets of Clustered Regularly Interspaced Short Palindromic Repeats Gene Editing

Abstract: The repurposing of the CRISPR/Cas bacterial defense system against bacteriophages as simple and flexible molecular tools has revolutionized the field of gene editing. These tools are now widely used in basic research and clinical trials involving human somatic cells. However, a global moratorium on all clinical uses of human germline editing has been proposed because the technology still lacks the required efficacy and safety. Here we focus on the approaches developed since 2013 to decrease the frequency of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…Since the death of mice was not related to the loss of function of the target genes, was it due to the defects of RfxCas13d itself? Off-target effects are an ongoing concern for gene editing using any CRISPR-Cas system [ 35 ]. Besides, collateral activity should be considered, although multiple studies have used RfxCas13d in vivo with no reported side effects [ 15 – 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the death of mice was not related to the loss of function of the target genes, was it due to the defects of RfxCas13d itself? Off-target effects are an ongoing concern for gene editing using any CRISPR-Cas system [ 35 ]. Besides, collateral activity should be considered, although multiple studies have used RfxCas13d in vivo with no reported side effects [ 15 – 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…It largely depends on the specificity of the introduced corrections (e.g., a proper selection of the target DNA site and the design of single guide RNA in the case of CRISPR/Cas technology), the choice of delivery method (e.g., vector integration ability) and the lack of off-target effects. The general drawbacks of existing genetic engineering techniques have been systemized in a series of comprehensive analyses [ 159 162 ] and are beyond the scope of this review. In relation to macrophages, it should be noted that the differentiation of iMphs from iPSCs goes through several stages, includes multiple rounds of cell division, takes at least 2–3 weeks to obtain the first iMph harvest and may last for many months afterwards.…”
Section: Imph-based Cell Therapy: Safety and Other Questions To Explorementioning
confidence: 99%
“…SpCas9 is the most widely used genome editor, owing to its robust activity in diverse cell types and less stringent PAM requirements. However, SpCas9 tends to display substantial off-target activities compared to other Cas nucleases [ 101 ]. Thus, Cas nucleases from other species, and dCas9- and nCas9-based genome editors that do not induce DSB (i.e., base editors and prime editors) have been extensively investigated for precise genome editing.…”
Section: Small-molecule Enhancers Of Precise Genome Editorsmentioning
confidence: 99%